Recent progress and future research directions for electrochromic zinc-ion batteries - Yun, Tae Gwang; Hwang, Byungil; Cheong, Jun Young (Journal of Energy Chemistry, 2024)
In recent times, future energy storage systems demand a multitude of functionalities beyond their traditional energy storage capabilities. In line with this technological shift, there is active research and development of electrochromic-energy storage systems designed to visualize electrochemical charging and discharging processes. The conventional electrochromic-energy storage devices primarily integrated supercapacitors, known for their high power density, to enable rapid color contrast. However, the low energy density of supercapacitors restricts overall energy storage capacity, acting as a significant barrier to expanding the application range of such systems. In this review, we introduce electrochromic zinc (Zn)-ion battery systems, which effectively overcome the limitation of low energy density, and provide illustrative examples of their applicability across diverse fields. Although many recent research works are present for electrochromic Zn-ion batteries, little review has so far taken place. Our objective is to discuss on the current progress and future directions for electrochromic Zn-ion batteries, which are applicable for wearable electronics applications and energy storage systems. This review provides an initial milestone for future researchers in electrochromic energy storage and zinc-ion batteries, which will lead to a stream of future works related to them.
Keywords: Conductive Polymer; Electrochromic zinc-ion battery; Electrochromics; Energy density; Flexible; Ion batteries; Lower energies; Storage systems; Transition-metal oxides; Zinc ions; Conductive polymer; Electrochromic Zn-ion battery; Flexible; Transition metal oxide